Value Added Tax (VAT), Gross Domestic Production (GDP) and Budget Deficit (BD): A Case Study in Sri Lanka. - Anojan, V. (University of Jaffna, 2015)
The focus of this study is to find out the impact of Value Added Tax (VAT) on Gross Domestic Production (GDP) and Budget Deficit (BD) of the country and also identify the association among value added tax, gross domestic production and budget deficit in Sri Lanka. Every country needs adequate tax revenue for their successful economic activities of their country. The tax revenue can be divided into two major categories such as direct and indirect tax revenue. Imposing the tax revenue is directly link with gross domestic production and budget deficit of the country. The indirect taxes generally impose on production, turnover, distribution of goods and services so indirect taxes directly link with gross domestic production of the country. Value added tax is one of the major indirect tax revenue of the Sri Lanka which was introduced in 2002 (Central Bank Report). Regression and correlation analysis were performed in this study with the help of SPSS latest version. Regression results confirmed that there is (R = 0.866) significant impact of value added tax on gross domestic production of the country and also there is (R = 0.705) significant impact of value added tax on budget deficit. Correlation results confirmed that there is (P = 0.000) significant association between value added tax and gross domestic production and also there is (P = 0.002) significant association between value added tax and budget deficit of the country. It implies that the Sri Lankan Government should give key focus on amending and implementation of VAT because the county is facing the budget deficit continuously and here the gross domestic production impact by VAT same time VAT impact on BD of the country. Also the high level of GDP needs for every country to improve the BD of the country so the government has to handle the value added tax very carefully for the economic success of the country.
Keywords: Budget Deficit; Gross Domestic Production; Sri Lanka; Value Added Tax